The New Politics of Fatherhood Men's Movements and Masculinities - Jordan, Ana (Genders and Sexualities in the Social Sciences, 2019)
This book makes a unique contribution to contemporary research into masculinities, men's movements, and fathers' rights groups. It examines the role of changing masculinities in creating equality and/or reinforcing inequality by analysing diverse men's movements, their politics, and the identities they (re)construct. Jordan advances a typology for categorising men's movements ('feminist', 'postfeminist', and 'backlash' movements) and addresses debates over the construction of 'masculinity-in-crisis', arguing that 'crisis' is frequently invoked in problematic ways. These themes are further explored through original analyses of material produced by 'feminist', 'postfeminist', and 'backlash' men's groups. The main empirical contribution of the book draws on interviews with fathers' rights activists to explore the (gendered) implications of the 'new' politics of fatherhood. The nuanced examination of fathers' rights perspectives reveals multiple, complex narratives of masculinity, fatherhood, and gender politics. The cumulative effect of these is, at best, postfeminist and depoliticising, and, at worst, another vitriolic 'backlash'. The New Politics of Fatherhood expands scholarly understandings of gender, masculinities, and social movements in the under-researched UK context, and will appeal to readers with interests in these areas.